Illicit Financial Flows on Africa’s Democratic Chain Governance - Ashok Kumar Katta; Murugan Ramu (International Journal of Supply Chain Management, 2018)
Illicit Financial Flows (IFFs) are a major challenge to Africas democratic governance. They have a direct impact on a countrys stability to raise, retain and mobilize its own resources to finance sustainable economic development. GFI (2017) finds that IFFs remain persistently high. The study finds that over the period between 2005 and 2014, IFFs on average accounted for between 14.1 percent and 24.0 percent of the total developing country trade, while outflows were estimated at 4.6 percent to 7.2 percent of total trade and inflows were between 9.5 percent and 16.8 percent. The problem with IFFs is that they are not only illicit but that their effect spreads far beyond their immediate area of occurrence. Millions of people are affected, economies are weakened, and development is stagnated, while a shady few accumulate wealth and influence. Financial flows are crucial for poor countries and have played an important role in most African countries that have made developmental progress. Since not all financial flows are good for development, the integration of poor countries into the global financial system poses opportunities as well as risks. IFFs usually facilitate most of these risks and have an overall negative impact on African countries.